Letter - Spain. Ejército Popular de la República. Brigada Internacional; Biheller, Frico
034-0011-001 No reply 90, Sutherland Ave. W.9. July 24th. 1942. Dear Sir/Madam, On behalf of the Group of Czechoslovak International Brigaders from Spain I take the liberty to invite you to the Commemoration of the Spanish War which will be organized by us on Friday, July 31st, 7.30 p.m. at the Conway Hall, Red Lion Sq. We want to demonstrate at this meeting the part the Czechoslovak and other International Brigaders played in the struggle against German and Italian intervention in Spain, by which the Axis Powers started their drive towards the domination of Europe. Our aim is to do our part in strengthening the anti-Nazi world alliance of all the nations, the foundations of which were laid, we are proud to say, by the International Brigades in Spain. There will be three Choirs which will sing songs of the International Brigades and the Spanish War. The addresses will be spoken by prominent representatives of the International Brigaders of various nationalities. A collection will take place, the proceedings of which will be used in aid of the International Brigaders still interned in France, Spain and North Africa. We should feel very much honoured indeed by your presence at this meeting, or - in case you could not attend - by a greeting from you and we should be very grateful for a gift for our interned comrades. I am yours faithfully Frico Biheller on behalf of the Czecheslovak International Brigaders. 292/946/34/11